Infrared Optical Wireless Communication for Underwater and Open-Air Environments: Design, Implementation, and Performance Analysis - Reena Durugwar; Dr. Sanket B. Kasturiwala; Dr. Devashree Marotkar; Shubham Hedau (Utilitas Mathematica, 2025)
Underwater Optical Wireless Communication (UOWC) is emerging as a promising technology for high-speed, low-latency data transmission in marine environments [1]. This paper presents a comprehensive study on the design, implementation, and experimental evaluation of a Peer-to-Peer (P2P) Infrared (IR) Optical Communication System for both underwater and open-air mediums [2]. The research aims to analyze the feasibility, performance, and limitations of IR-based optical communication by examining critical parameters such as signal attenuation, transmission range, data rate, bit error rate (BER), and the impact of environmental factors on communication efficiency [3]. The experimental setup involves the use of infrared light sources and photodetectors to establish a wireless communication link [5]. Controlled tests were conducted in different water conditions, including clear, coastal, and turbid waters, to evaluate the effects of scattering, absorption, and refraction on signal propagation [6], [7]. Comparative studies were also performed in an open-air medium to benchmark underwater communication performance against terrestrial optical communication [8]. The findings indicate that IR-based optical communication offers high data rates and low latency compared to acoustic and RF-based underwater communication systems . However, challenges such as alignment sensitivity, high attenuation in turbid waters, and limited transmission distance were observed [11]. To enhance system efficiency, the study explores potential optimization strategies, including beam shaping, adaptive modulation techniques, and the use of optical filters to mitigate noise and improve signal detection. The research also compares the experimental results with theoretical models to validate the feasibility of real-world deployment. The insights gained from this study contribute to the development of next-generation UOWC systems with applications in marine exploration, underwater sensor networks, remotely operated vehicles (ROVs), and defense communication systems . Future work will focus on enhancing system robustness, expanding transmission range, and integrating AI-driven adaptive signal processing techniques to improve underwater communication reliability further [17].